The bond strength of reinforced concrete with confinement of recycled steel strap. (1st October 2022) - Sulaiman, Muhd Fauzy; Chin, Chee-Loong; Ma, Chau-Khun; Awang, Abdullah Zawawi; Omar, Wahid
Abstract: The potential use of recycled steel strap from packaging industry to strengthen bond between reinforcement steel and concrete was investigated. Through a series of pull-out experimental tests, this technique was shown to improve the bond properties between reinforcement steel and concrete. This research found that concrete strength and amount of steel straps provided for confinement affect the improvements on the bond between reinforcement steel and concrete. The analysis conducted in this research found that higher concrete strength and less amount of steel strap confinement would result in lower improvement in the bond strength. Subsequently, the effects of concrete strength and amount of steel strap confinement provided were considered into a newly developed equation to estimate bond strength. This research also conducted a model assessment on the proposed equation and the equation was found to be in good agreement with the experimental test results.